2019
DOI: 10.1016/j.biopsych.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Remodels Synapses in an Amygdala Circuit–Specific Manner

Abstract: Chronic stress caused BLA PN neuronal remodeling with a previously unrecognized degree of circuit specificity, offering new insight into the pathophysiological basis of depression, anxiety disorders, and other stress-related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 64 publications
6
91
1
1
Order By: Relevance
“…Dendritic spines are important locations for the formation of neuronal circuits and network structures. A reduction in dendritic spine density is bound to reduce synapse formation and thus impair cognitive function [43]. Our previous study showed that CCH can lead to a reduction in dendritic spines.…”
Section: Resultsmentioning
confidence: 99%
“…Dendritic spines are important locations for the formation of neuronal circuits and network structures. A reduction in dendritic spine density is bound to reduce synapse formation and thus impair cognitive function [43]. Our previous study showed that CCH can lead to a reduction in dendritic spines.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, it will be important to perform similar mitochondrial analyses as the ones included in the current study to investigate chronic stress effects in other brain regions critically involved in the brain response to chronic stress and MDD, such as the orbitofrontal cortex (OFC), hippocampus and amygdala 74 , 75 . These studies will be particularly relevant to understand the link between mitochondria and stress-induced changes in neuronal structure as, in contrast to the hypotrophy induced by stress in the medial PFC 47 50 or in the hippocampus 76 , 77 , the basolateral amygdala 78 (but see 79 ) and the OFC show dendritic hypotrophy 80 following similar stress protocols. In addition, future functional studies will be needed to elucidate the underlying molecular mechanisms of how the herein defined mitochondrial gene expression changes can act as a vulnerability factor for the development and/or pathology of stress-induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…Some, but not all, chronic stress paradigms increase activity in the BLA (Shepard et al, 2016;Lowery-Gionta et al, 2018;Zhang et al, 2019), enhancing excitatory output at BLA-to-PFC synapses and inducing an anxiety phenotype. Whether a stress-induced increase in excitatory BLA projections to the PFC is driving the activity of prefrontal PV cells remains to be determined.…”
Section: Macrocircuit Inputs Possibly Driving Gabaergic Changes In Thmentioning
confidence: 99%
“…Whether a stress-induced increase in excitatory BLA projections to the PFC is driving the activity of prefrontal PV cells remains to be determined. Chronic stress also increases spine density and glutamatergic signaling in BLA projections to the ventral hippocampus, increasing activity of this region (Zhang et al, 2019). The ventral hippocampus directly innervates the PFC and excites PV interneurons (Gabbott et al, 2002;Caballero et al, 2014b).…”
Section: Macrocircuit Inputs Possibly Driving Gabaergic Changes In Thmentioning
confidence: 99%